Hadgyakorlat fegyver nélkül . Military exercise without weapons ([Budapest], 1977)
To study the samples collected from the contaminated area, the experts use the latest measuring devices. Since the protection of agriculture forms a very important part of civil defense, we should be familiar with the techniques available: both the traditional methods and the new ones that use specialized machinery. We should have detailed knowledge of the procedure for decontaminating animals, and must also be aware that in some cases their immediate slaughter is the best solution. A similarly important task is the NBC protection of goods during transportation. A szennyezett környezetből vett mintát szakértői vizsgálatnak vetik alá. Ehhez a korszerű mérőműszerek rendelkezésre állnak. A mezőgazdaság megóvása fontos része a polgári védelemnek, ezért ismerni kell annak szakszerű módját, legyen az a hagyományos, vagy akár célgépekkel történő mentés. Tisztában kell lenni az állatok mentesítési eljárásának részleteivel, szükség esetén szakszerűen végzett kényszervágáshoz kell folyamodnunk. Tisztában kell lennünk az áruk szállítás közbeni RBV-védelmének módjával is.